Investigation of the stress corrosion cracking resistance of SAF2205 and AISI304 weldments for the marine environment application - Matjee, Mapula Regina (Department of Mechanical Engineering, 2021)
Stainless steels are used for many industrial applications because of their strength and fabrication characteristics. Stainless steel grades of SAF2205 and AISI304 can readily meet a wide range of design criteria of service life, maintenance, load and corrosion resistance.